2023
DOI: 10.3390/vaccines11030693
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Disease in Under-5 Children: Current Status and Strategies for Prevention including Vaccination

Abstract: Since the coronavirus disease (COVID-19) pandemic hit the globe in early 2020, we have steadily gained insight into its pathogenesis; thereby improving surveillance and preventive measures. In contrast to other respiratory viruses, neonates and young children infected with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) have a milder clinical presentation, with only a small proportion needing hospitalization and intensive care support. With the emergence of novel variants and improved testing serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 210 publications
(211 reference statements)
0
3
0
Order By: Relevance
“…Moreover, WHO [ 40 ] reported that during the initial pandemic phase with the ancestral strain, from December 2019 to October 2021, children under five years of age represented 2% of reported global cases and 0.1% of reported global deaths. According to a recent review study, key mechanisms that protect young children from severe COVID-19 disease include the placental barrier, differential expression of angiotensin-converting enzyme 2 (ACE-2) receptors, immature immune response, and passive transfer of antibodies via placenta and human milk [ 41 ]. Older children and younger adolescents (5 to 14 years) account for 7% of reported global cases and 0.1% of reported global deaths.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, WHO [ 40 ] reported that during the initial pandemic phase with the ancestral strain, from December 2019 to October 2021, children under five years of age represented 2% of reported global cases and 0.1% of reported global deaths. According to a recent review study, key mechanisms that protect young children from severe COVID-19 disease include the placental barrier, differential expression of angiotensin-converting enzyme 2 (ACE-2) receptors, immature immune response, and passive transfer of antibodies via placenta and human milk [ 41 ]. Older children and younger adolescents (5 to 14 years) account for 7% of reported global cases and 0.1% of reported global deaths.…”
Section: Discussionmentioning
confidence: 99%
“…Among general and specific advantages of vaccination during pregnancy, the primary ones are the prevention of maternal morbidity and mortality and the reduction of risks of intrauterine infection and fetal disease [ 38 ]. The key mechanism that protects neonates from severe infective diseases is associated with the passive transfer of antibodies via the placenta and human milk [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 ] Since the outbreak of the SARS-CoV-2 in 2019, >600 million people have been infected, resulting in >6 million deaths worldwide. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%